SOCIAL CONFLICTS AND POLITICAL TRANSFORMATION IN EARLY TRAVANCORE - ASHA RAJAN
In 1947, when India was on the threshold of attaining independence, the attitude of the princely states underwent certain changes) The decision of the British Government to transfer power to India, leaders left the states free either to join the Dominion of India or the Dominion of Pakistan or to stand independent. The administration decided to declare Travancore as an independent state from the day of British withdrawal from India. This daring venture, undertaken by the Diwan and the Maharaja in disregard to public opinion complicated the political situation. The congress leaders of India including Gandhi vehemently condemned this policy of the Diwan. The state congress on the other hand, launched an agitation in June 1947 against this move. The formation of Travancore Constituent Assembly was remarkable in many respects. It marked the death knell of monarchy and the dawn of democracy. Travancore got the credit for conducting elections on the basis of universal adult suffrage for the first time in an Indian State. But it also marked the dawn of communalism and power games, indicative of the fact that it was the dress rehearsal of democracy and popular governance in Kerala.